Social Ontology for All (Kinds of Groups). (9th March 2019) - Moltchanova, Anna
Abstract: Contemporary theories of institutional group agency have focused on modeling democratically legitimate institutional group agents. Yet many countries in the world are democratic only on paper, with their governing structures relying, to a large extent, on informal power networks. I give a paradigmatic example of the governance in a de facto nondemocratic state based on sistema, and then explain how we can model something like a sistema- based group to reflect both its differences with widely theorized liberal-democratic groups and its status with respect to its members.